2015
DOI: 10.1371/journal.pone.0120841
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Drugs to Treat 8p11 Myeloproliferative Syndrome Using Patient-Derived Induced Pluripotent Stem Cells with Fusion Gene CEP110-FGFR1

Abstract: Induced pluripotent stem (iPS) cells provide powerful tools for studying disease mechanisms and developing therapies for diseases. The 8p11 myeloproliferative syndrome (EMS) is an aggressive chronic myeloproliferative disorder (MPD) that is caused by constitutive activation of fibroblast growth factor receptor 1. EMS is rare and, consequently, effective treatment for this disease has not been established. Here, iPS cells were generated from an EMS patient (EMS-iPS cells) to assist the development of effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Nonetheless, this frequency exceeds many other genetic events seen in AML. Overexpression of FGFR1 is also the driver of SCLL, which is similarly sensitive to anti-FGFR1 therapies [18, 3638]. The presence of FGFR1 overexpression in these AML, however, was confirmed using quantitative PCR, unlike those in the databases.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this frequency exceeds many other genetic events seen in AML. Overexpression of FGFR1 is also the driver of SCLL, which is similarly sensitive to anti-FGFR1 therapies [18, 3638]. The presence of FGFR1 overexpression in these AML, however, was confirmed using quantitative PCR, unlike those in the databases.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the third‐generation TKI ponatinib has been demonstrated to inhibit phosphorylation levels of various FGFR1‐fusion kinases and their downstream effector functions, resulting in cell growth inhibition and cell death in vitro . Induced pluripotent stem cells generated from a patient with EMS with CEP110‐FGFR1 formed reduced colony‐forming unit numbers when treated with CHIR258 (dovitinib), PKC 412 (midostaurin), and ponatinib, but not with imatinib, and similar effects were observed in vitro for this patient's blood cells . Finally, a partial response to ponatinib has recently been reported in a 47‐year‐old patient with BCR‐FGFR1 ‐positive mixed‐phenotype leukemia who was subsequently rescued with repeat inductions with methotrexate and cytarabine followed by allogeneic HCT .…”
Section: Case Reportmentioning
confidence: 59%
“…Dovitinib (CHIR258, TKI258) is a multitarget receptor tyrosine kinase inhibitor with activity against class III, IV, and V receptor tyrosine kinases, such as VEGFRs, FGFRs, PDGFRs, FLT3, KIT, and CSF-1R. This molecule is currently being tested in a phase III clinical trial for renal cell carcinoma, and phase II clinical trials for advanced breast and endometrial cancers, relapsed multiple myeloma, and urothelial cancer [31]. Studies assessing MYM2-FGFR1-or BCR-FGFR1-transformed Ba/F3, KG1, and KG1A AML cell lines (FGFR1OP2-FGFR1) as well as primary cells from EMS patients demonstrated that TKI258 inhibits cell proliferation at low nanomolar concentrations [32,33].…”
Section: Discussionmentioning
confidence: 99%